Pelatihan Praktis Manajemen Sasaran Kinerja Pegawai (e-SKP) untuk Tenaga Kependidikan di Fakultas Ekonomi dan Bisnis Universitas Cenderawasih - Boy Piter Nizu Kekri; Franslin Dewi Arianiningsih; Endro Risdiyanto (Lembaga Pengembangan Kinerja Dosen, 2025)
This Community Service Program aims to enhance the practical abilities of educational staff in understanding and implementing the Electronic Employee Performance Target (e-SKP) system within the Faculty of Economics and Business, Cenderawasih University. The training program was designed to meet the needs of staff for practical knowledge regarding digital performance appraisal systems in accordance with the latest civil service regulations. The training applied an andragogical approach, emphasizing adult learning experiences through simulations, focused group discussions, and hands-on practice in using the e-SKP application. The resource person, Sukrisman, S.T., M.Cs., provided technical guidance and interactive assistance throughout the activity. The results indicated an improvement in participants’ knowledge and skills in operating the e-SKP application, as evidenced by their ability to independently prepare performance reports and actively engage in evaluation discussions. Moreover, participants gained a better understanding of the relationship between job descriptions, positions, and daily logs with performance indicators measured through e-SKP. Future development of this program will focus on implementing a study-program-based approach and integrating the e-SKP system with the faculty’s overall performance planning framework.